2019
DOI: 10.1007/s40259-019-00344-7
|View full text |Cite|
|
Sign up to set email alerts
|

Vestronidase Alfa: A Review in Mucopolysaccharidosis VII

Abstract: Mucopolysaccharidosis VII is an extremely rare, autosomal recessive lysosomal storage disorder characterized by a deficiency of β-glucuronidase activity, resulting in partial degradation and accumulation of GAGs in numerous tissues throughout the body, with consequent cellular damage and organ dysfunction. Enzyme replacement therapy (ERT) with intravenous vestronidase alfa (Mepsevii™), a recombinant form of human β-glucuronidase, is the first disease-specific therapy approved for the treatment of mucopolysacch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…LSDs are a group of about 50 inborn errors of metabolism (IEM) characterized by the lysosomal accumulation of partially or non-degraded molecules. Therapies for LSDs treatment may include: (1) to promote the storage clearance by administering an exogenous functional enzyme, (i.e., ERT); (2) to prevent the lysosomal accumulation of substrates by inhibiting their synthesis (i.e., substrate reduction therapy); (3) to enhance the enzyme activity of a mutated protein (i.e., PC therapy); and (4) to perform a bone marrow or stem cell transplantation, especially in those diseases with central nervous system (CNS) involvement [30][31][32][33][34][35][36]. Molecular characterization of LSDs has shown that in most of the cases the disease is caused by missense mutations [37,38].…”
Section: Use Of Pharmacological Chaperones In Lsdsmentioning
confidence: 99%
“…LSDs are a group of about 50 inborn errors of metabolism (IEM) characterized by the lysosomal accumulation of partially or non-degraded molecules. Therapies for LSDs treatment may include: (1) to promote the storage clearance by administering an exogenous functional enzyme, (i.e., ERT); (2) to prevent the lysosomal accumulation of substrates by inhibiting their synthesis (i.e., substrate reduction therapy); (3) to enhance the enzyme activity of a mutated protein (i.e., PC therapy); and (4) to perform a bone marrow or stem cell transplantation, especially in those diseases with central nervous system (CNS) involvement [30][31][32][33][34][35][36]. Molecular characterization of LSDs has shown that in most of the cases the disease is caused by missense mutations [37,38].…”
Section: Use Of Pharmacological Chaperones In Lsdsmentioning
confidence: 99%
“…A pivotal phase-III trial on vestronidase alfa has shown a significant decrease in urinary CS-DS excretion after 24 weeks [5]. While a marked amelioration of organomegaly and fatigue was observed, only a relative improvement in the mobility and the respiratory functions was noted [5].…”
Section: Discussionmentioning
confidence: 99%
“…A pivotal phase-III trial on vestronidase alfa has shown a significant decrease in urinary CS-DS excretion after 24 weeks [5]. While a marked amelioration of organomegaly and fatigue was observed, only a relative improvement in the mobility and the respiratory functions was noted [5]. The recombinant enzyme is directly infused into the bloodstream allowing its delivery to peripheral organs except for the brain, because of its inability to cross the blood-brain barrier.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…substrate reduction therapy), 3) to enhance the enzyme activity of a mutated protein (i.e. PC therapy), and 4) to perform a bone marrow or stem cell transplantation, especially in those diseases with central nervous system (CNS) involvement [30][31][32][33][34][35][36]. Molecular characterization of LSDs has shown that in most of the cases the disease is caused by missense mutations [37,38].…”
Section: Use Of Pharmacological Chaperones In Lsdsmentioning
confidence: 99%